Senhora Hermosa Bakery / Nuratiqah Raihana Ahmad Ramzi - Ahmad Ramzi, Nuratiqah Raihana (2019)
Senhora Hermosa Bakery promises a value lifestyle proposition of great variety and quality cakes and pastry at affordable prices. The uncompromising quality of cake and pastry using quality ingredients, coupled with moderate pricing, has created a new lifestyle cult, comprising of a loyal base of pastry and cake lovers. The plan of Senhora Hermosa Bakery, as the business growth, is expanding the business branching in several states in Malaysia and creating the company types of bread and cake which has it own benchmarking. And lastly, the company is getting recognized in the bakery industry and admits as the one of famous bakery in Malaysia.